2017
DOI: 10.12691/ajmr-5-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antimicrobial Effectiveness of Two Medicated Soaps with Herbal Soap from <i>Morinda morindoides </i>(Rubiaceae) against Skin Pathogens

Abstract: In present study two medicated soaps namely Pharmaderm and Micoderme and herbal soap Morinda formulated with fat extracted from leaves of Morinda morindoides (Rubiaceae) were investigated for their antimicrobial activities against some clinical strains for skin.diseases. The purpose of this study was to verify and compare their antimicrobial effectiveness. Agar broth dilution method with Sabouraud and Mueller-Hinton at serial concentrations of soaps ranging from 62.50 to 3.9 mg/ml and agar plate method were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The traditional use of the leaves of this plant in other African countries has been described [8]. The fractions obtained from the leaf extract by solvent partition have been reported to possess antiplasmodial activity [9], anti-microbial activities against some skin diseases [10], and anti-fungal activity [11] by in vitro assay. Extensive phytochemical research on the leaves has identi ed avonoids [12], iridoids [13,14], and anthraquinones [15], and on the roots has identi ed ketosteroid [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional use of the leaves of this plant in other African countries has been described [8]. The fractions obtained from the leaf extract by solvent partition have been reported to possess antiplasmodial activity [9], anti-microbial activities against some skin diseases [10], and anti-fungal activity [11] by in vitro assay. Extensive phytochemical research on the leaves has identi ed avonoids [12], iridoids [13,14], and anthraquinones [15], and on the roots has identi ed ketosteroid [16].…”
Section: Introductionmentioning
confidence: 99%
“…)[35]; two megastigmanes, (+)-(6R,9S)-blumenol C (8)[36] and (+)-(6S,9R)-blumenol B (9)[37]; and two avonol 3-O-glycosides, astragalin(10) [38] and rutin(11) [39]. Moreover, in our preliminary study, the peak of oleanolic acid(12) -for which anti-malarial activity has been reported[40,41] -was detected (m/z 457.3662 [M + H] + and 455.3554 [M-H] − ) in both MeOH and EtOH extracts in the less polar part by LC/MS.…”
mentioning
confidence: 99%